2012
DOI: 10.1002/pro.2045
|View full text |Cite
|
Sign up to set email alerts
|

Thermal coefficients of the methyl groups within ubiquitin

Abstract: Physiological processes such as protein folding and molecular recognition are intricately linked to their dynamic signature, which is reflected in their thermal coefficient. In addition, the local conformational entropy is directly related to the degrees of freedom, which each residue possesses within its conformational space. Therefore, the temperature dependence of the local conformational entropy may provide insight into understanding how local dynamics may affect the stability of proteins. Here, we analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 46 publications
3
33
1
Order By: Relevance
“…In contrast to previous studies of methyl dynamics across different temperatures, a particularly sharp temperature dependence of Oaxis2 is observed, with an average value of −5.9 ± 1.5 × 10 −3 K −1 across methyl residues. This value is significantly larger than that in previous studies on ubiquitin and a calmodulin–peptide complex, where the observed d Oaxis2/d T values were −2.3 and −2.5 × 10 −3 K −1 , respectively .…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to previous studies of methyl dynamics across different temperatures, a particularly sharp temperature dependence of Oaxis2 is observed, with an average value of −5.9 ± 1.5 × 10 −3 K −1 across methyl residues. This value is significantly larger than that in previous studies on ubiquitin and a calmodulin–peptide complex, where the observed d Oaxis2/d T values were −2.3 and −2.5 × 10 −3 K −1 , respectively .…”
Section: Resultscontrasting
confidence: 99%
“…The average temperature derivative of the Oaxis2 values obtained in the solid state data is −2.2 ± 1.2 × 10 −3 K −1 and compares with −5.9 ± 1.5 × 10 −3 K −1 obtained in solution. Interestingly, the slope of the solid state data correlates very well with previous studies of temperature‐dependent methyl dynamics in the solution state . Significant differences between the solution and solid‐state lambda values for HP36 are seen (Fig.…”
Section: Resultssupporting
confidence: 87%
“…In order to find out if the A147T substitution influences the motional properties of the side chains of mTSPO and thus modulates the entropic component of the interaction with PK11195, we probed the dynamics of the methyl groups of mTSPO in complex with (R)-PK11195. Cross-correlated relaxation rates (σ obs ) between dipolar couplings of two CH bonds were measured for well separated cross peaks in 2D 1 H-13 C HSQC spectra [21]. 19 methyl groups distributed across the entire structure could be analyzed ( Figure 3A and Supporting Information Figure S3).…”
Section: Mobility Of the Side Chains Of Tspo In Complex With Pk11195mentioning
confidence: 99%
“…19 methyl groups distributed across the entire structure could be analyzed ( Figure 3A and Supporting Information Figure S3). As more rigid methyl groups have larger σ obs rates [21], the methyl groups of A50, I52 and L56 are most rigid. Moreover, comparison of σ obs rates between wild-type protein and the A147 variant showed that the motional properties of the methyl groups were retained despite the A147 substitution ( Figure 3A).…”
Section: Mobility Of the Side Chains Of Tspo In Complex With Pk11195mentioning
confidence: 99%
See 1 more Smart Citation